Analisis Yuridis Pengaturan Perpindahan Atlet E-Sports Pada Olahraga E-Sports Di Indonesia - Imanuel Mario; I Gede Putra Ariana (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The purpose of this study is to examine the analysis of player transfer arrangements that occur in e-Sports sports in Indonesia by reflecting on the positive law that applies in Indonesia and also what underlies the legal relationship between e-Sports athletes and the team that has just bought them. This study uses normative legal research methods with a statutory approach and other secondary materials. The results of this study show that regulations regarding the transfer of both athletes as athletes and athletes as workers have been regulated in the Sports Law, Employment Law, and Indonesian Esports Executive Board Regulation Number: 034/PB-ESI/B/VI/2021. And the thing that underlies the legal relationship between an e-Sports athlete who moves from one e-Sports team to another is a contract or work agreement made based on the Civil Code.